Suomen museo. 1978 : 85. vuosikerta - Linkola, Martti; Núňez, Milton G.; Torvinen, Markku; Väkeväinen, Lea.; Vuoristo, Osmo.; Lilius, Henrik; Sinisalo, Jaakko (Helsinki : Suomen muinaismuistoyhdistys, 1979)
Sis. eng. tiivistelmät
suomi
KIRJA / BOK
Keywords: Granstedt, Pehr; Engel, C. L; 1978; museot; historia; esihistoria; arkeologia; kansatiede; muinaisesineet; muinaisjäännökset; kalmistot; savi; rakennusaineet; Heidenstrauchin talo; Presidentinlinna; Suomi; Lieto; Mynämäki; Pori; Helsinki; vuosikirjat